Marcella Wells packing historic clothing - Unidentified photographer (Colorado State University. Libraries, 2000)
Photograph of Marcella Wells, volunteer, packing historic clothing into an archival box during a May 2000 storage update project, funded by an Institute of Museum and Library Services grant. Wells is leaning over an open box that extends the length of the table.
Keywords: Fashion -- History; Fashion -- Exhibitions